Crisis management for euro-area banks in central Europe - Alexander Lehmann (Bruegel, 2019)
The deep involvement of a number of euro-area banking groups in central and southeastern Europe has benefi tted the host countries and has strengthened the resilience of those banking groups. But this integration has become less close because of post-fi nancial crisis national rules that require banks to hold more capital at home, or other ring-fencing measures. Th ere is a risk integration might be undermined further by bank resolution planning, which is now gathering pace. Regulators and banks will need to decide between two distinct models for crisis resolution, and this choice will redefi ne banking networks. Most effi cient in terms of preserving capital and the close integration of subsidiary operations would be if the Single Resolution Board - the banking union's central resolution authority - takes the lead for the entire banking group. However, this will require parent banks to hold the subordinated debts of their subsidiaries. Persistent barriers to intra-group capital mobility - or the option for home or host authorities to impose such restrictions - will ultimately render such schemes unworkable. The second model would involve independent local intervention schemes, which European Union countries outside the banking union are likely to call for. Th is will require building capacity in local debt markets, and clarifying creditor hierarchies. Exposure to banking risks will ultimately need to be borne by host-country investors. Bail-in capital issued by subsidiaries to their parents cannot be a substitute because it would expose the home country to fi nancial contagion from the host. To sustain cross-border linkages, banking groups and their supervisors will need to make bank recovery plans more credible, and to strengthen cooperation in resolution colleges (platforms that bring together all relevant parties in resolution planning and execution). Within the banking union there is no justifi cation for the various ring-fencing measures that have impeded the fl ow of capital and liquidity within banking groups.
Keywords: 330